Student perceptions of the transfer support systems offered at two- and four-year institutions - Passow, Teri (My University, 2010)
As the number of transfer students increased across the country, it is important to continue to learn about the transfer process. This qualitative study explored the support systems made available to students transferring from a two- to four-year campus. To investigate the transfer transition, this research utilized the following question: What perceptions do students have of the transfer support systems offered at two-and four-year institutions? Nine students, seven staff members from two-year campuses, and five staff members from a four-year institution participated in the study. Data gathered during these interviews was analyzed using a constant comparative method. While separate themes were identified for each group of participants, four major conclusions emerged in the complete analysis: communication, types of support, levels of support, and overall transfer experience. Considering these conclusions, several recommendations and ideas for future research are provided. These observations and suggestions will assist two- and four-year campuses in providing more complete support systems for transfer students in the future.
Keywords: College students; Transfer students -- Services for